Computer-Assisted Vocational Life Skills Program for Offenders - Quigley, M.; Jeffery, Gary H.; McNutt, Marvin (Canadian Journal of Counselling and Psychotherapy, 1993)
Deficits in social-cognitive skills are deemed to be a major problem for many offenders. The development of a computer-based software package designed to support existing life-skills training programs is outlined. The program is based on extensive field data collected from life- skills instructors. The data and the models upon which the product is based are described along with the prototype package.